PERSEPSI DAN SIKAP MAHASISWA UMRI TERHADAP EDUCATION FOR SUSTAINABLE DEVELOPMENT (ESD) DALAM IMPLEMENTASI ECOCAMPUS - Ilham Hudi; Hadi Purwanto; Diah Retno; Dian Hafizah Triana (Universitas Muria Kudus, 2022)
The purpose of this study was to find out how the perceptions of Accounting and Science education students at Muhammadiyah Riau University towards Education for Sustainable Development (ESD).The research method used is a quantitative method and is based on a survey. Data collection was carried out by distributing questionnaires and interviews with 70 people. The questionnaire was developed by including part of the idea of education for sustainable development into each item, which was assessed on a five-point Likert scale. The sampling method uses stratified random sampling and the Slovin formula to determine the number of samples. Students' perceptions of socio-cultural aspects scored 85.07% (very good), environmental aspects scored 81.71% (very good), and economic aspects scored 82.62% (very good).The results of the study found that Accounting and Science Education students at Muhammadiyah University of Riau on Education for Sustainable Development/ESD got a score of 83.13%. This can be seen in the behavior of students who have started to bring their own drinking bottles, some students have also started using eco-friendly straws, carrying out environmental activities such as planting trees, student participation in campus decision making, and so on. This activity helps the implementation of Ecocampus which enables institutions to contribute to meeting sustainable development goals at the same time.